2019
DOI: 10.1093/pch/pxz001
|View full text |Cite
|
Sign up to set email alerts
|

Support, information, and integration of genetics for children with congenital lower limb deficiencies in British Columbia, Canada

Abstract: Objectives Children and families affected by congenital limb deficiencies (CLD) require a unique level of emotional support from diagnosis through to adolescence. The following study aims to collect data on Canadian paediatric patients affected by a CLD followed at BC Children’s Hospital (BCCH), Department of Orthopaedics. Methods Parents of children with a CLD were asked to complete a written questionnaire examining their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…To chart and extract data from the articles selected for the scoping review, an extraction criterion was developed by 2 reviewers (AG and MT) to extract information from each publication about the study country, city, urban or not urban geography, population, sample size, age of participants, pediatric disease types, duration, demographic information, design, methodology, journal of publication, and results of the study (Multimedia Appendix 2 [3,12,16,[33][34][35][36][37][38][39][40][41][42][43]).…”
Section: Data Items and Data Charting Processmentioning
confidence: 99%
See 4 more Smart Citations
“…To chart and extract data from the articles selected for the scoping review, an extraction criterion was developed by 2 reviewers (AG and MT) to extract information from each publication about the study country, city, urban or not urban geography, population, sample size, age of participants, pediatric disease types, duration, demographic information, design, methodology, journal of publication, and results of the study (Multimedia Appendix 2 [3,12,16,[33][34][35][36][37][38][39][40][41][42][43]).…”
Section: Data Items and Data Charting Processmentioning
confidence: 99%
“…Of the 14 studies, 5 (36%) studies included populations where children were clinically diagnosed with various genetic conditions [16,[33][34][35][36]; 4 (29%) studies had populations that were not diagnosed with an illness [12,[37][38][39]; 1 (7%) study included children who were suspected to have a genetic condition but not diagnosed [40]; 1 (7%) study included children who were hospitalized for various reasons [3]; and the remaining 3 (21%) studies reported pediatric populations with illnesses such as cancer [41], congenital heart defects [42], and congenital lower limb deficiencies [43]. Most (11/14, 79%) of the studies selected for the review were from the United States [3,12,[33][34][35][36][38][39][40][41][42], 14% (2/14) from Canada [16,43] and 7% (1/14) from the United Kingdom [37]. Table 1 presents the overview of the included studies.…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations